Obsessive compulsive disorder (ocd) as a severe mental health disorder: A concise review of management with radiosurgery for intractable disease - Omer Sager; Murat Beyzadeoglu; Ferrat Dincoglan; Selcuk Demiral; Bora Uysal; Hakan Gamsiz; Fatih Ozcan; Onurhan Colak; Bahar Dirican (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Obsessive Compulsive Disorder (OCD) is a mental health disorder with characteristic features including uncontrollable, reoccurring thoughts referred to as obsessions, and excessive urges to perform repeated certain routines referred to as compulsions. Affected patients may suffer from tics, anxiety, negative social behaviours and self mutilation. Symptoms of patients may be intrusive, anxiety-provoking, and rather distressing which may significantly compromise both social and occupational functioning. Deterioration in quality of life may occur as a consequence of unemployment, marriage failure, and maladjustment in familial relationships. Initial management of OCD may include exposure and response prevention, cognitive-bahavioural-therapy, and pharmacological agents such as selective serotonin reuptake inhibitors and tricyclic antidepressants. These management strategies may be effective for the majority of patients suffering from OCD. However, approximately 20% of patients have refractory OCD unresponsive to first-line therapies and a subgroup of patients unresponsive to first-line therapies suffer from severe debilitating symptoms referred to as intractable OCD. Radiosurgery has a long history as an excellent radiotherapeutic modality for management of several intracranial disorders. Radiosurgical or gamma capsulotomy technique involving discrete, circumscribed lesions in white matter of the anterior limb of the internal capsule has been introduced by the Swedish neurosurgeon Lars Leksell. Gammaknife Radiosurgery (GKRS) system has been used as a viable alternative to open surgical anterior capsulotomy procedures and gained popularity and widespread acceptance with accumulating evidence from several centers worldwide. Herein, we provide a concise review including the definition, epidemiology and symptomotology of OCD, patient selection criteria, and management options with focus on radiosurgery.